A Case-Control Study for Assessing Risk Factors for Congenital Anomalies among Children in Sulaimani City - Mustafa Kamal, Niaz; Othman, Nasih (Kurdistan Journal of Applied Research, 2018)
Congenital anomalies comprise a wide range of abnormalities in body structure or function that are present at birth and are of prenatal origin. These are defined as structural changes that have significant medical, social or cosmetic consequences for the affected individual, and typically require medical intervention. According to our Knowledge, research is scarce on these conditions in Sulaimaniyah city. Therefore, the current study was conducted to investigate potential risk factors for congenital anomalies. A case-control study was carried out from March to August 2017 involving 400 children (200 cases and 200 controls) aged 0-5 years. Required data were obtained on the risk factors through face to face interviews with mothers of cases and controls. The data were using descriptive statistical methods, Chi-square and Logistic Regression using STATA 11, calculating odds ratios and condensing P value less than 0.05 as statistically significant. The mean age of the children was 1.9 years and age of their mothers at the time of pregnancy was 28 years. Congenital heart anomalies were the commonest type accounting for 27.5%. Significant risk factors for congenital anomalies were family history (OR=2.24, P= 0.007), maternal obesity (OR= 2.26, P= 0.001), mothers age over 30 (OR=2.78, P= 0.002) and mothers not using folic acid during pregnancy (OR=2.12, P= 0.0007). In general, in order to control and prevent the cases of CM, it is important to provide health education and policies to reduce environmental and maternal risk factors. Further, studies with larger sample size are needed to investigate incidence and risk factors of congenital anomalies.